Phosphoproteome analysis reveals the involvement of protein dephosphorylation in ethylene-induced corolla senescence in petunia - Shiwei Zhong (BMC, 2021)
Abstract Background Senescence represents the last stage of flower development. Phosphorylation is the key posttranslational modification that regulates protein functions, and kinases may be more required than phosphatases during plant growth and development. However, little is known about global phosphorylation changes during flower senescence. Results In this work, we quantitatively investigated the petunia phosphoproteome following ethylene or air treatment. In total, 2170 phosphosites in 1184 protein groups were identified, among which 2059 sites in 1124 proteins were quantified. To our surprise, treatment with ethylene resulted in 697 downregulated and only 117 upregulated phosphosites using a 1.5-fold threshold (FDR < 0.05), which showed that ethylene negatively regulates global phosphorylation levels and that phosphorylation of many proteins was not necessary during flower senescence. Phosphoproteome analysis showed that ethylene regulates ethylene and ABA signalling transduction pathways via phosphorylation levels. One of the major targets of ethylene-induced dephosphorylation is the plant mRNA splicing machinery, and ethylene treatment increases the number of alternative splicing events of precursor RNAs in petunia corollas. Conclusions Protein dephosphorylation could play an important role in ethylene-induced senescence, and ethylene treatment increased the number of AS precursor RNAs in petunia corollas.